2016
DOI: 10.1128/jcm.02864-15
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Oxacillin and Cefoxitin Disk and MIC Breakpoints for Prediction of Methicillin Resistance in Human and Veterinary Isolates of Staphylococcus intermedius Group

Abstract: Staphylococcus pseudintermedius is a coagulase-positive species that colonizes the nares and anal mucosa of healthy dogs and cats. Human infections with S. pseudintermedius range in severity from bite wounds and rhinosinusitis to endocarditis; historically, these infections were thought to be uncommon, but new laboratory methods suggest that their true incidence is underreported. Oxacillin and cefoxitin disk and MIC tests were evaluated for the detection of mecA-or mecC-mediated methicillin resistance in 115 h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
91
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 77 publications
(99 citation statements)
references
References 28 publications
6
91
2
Order By: Relevance
“…If the colony morphotypes observed at F1 bred true to the F2 plate, these were tested independently. Each colony morphotype was evaluated for the presence of mecA by PCR in one laboratory, using a method described previously (16).…”
Section: Methodsmentioning
confidence: 99%
“…If the colony morphotypes observed at F1 bred true to the F2 plate, these were tested independently. Each colony morphotype was evaluated for the presence of mecA by PCR in one laboratory, using a method described previously (16).…”
Section: Methodsmentioning
confidence: 99%
“…44 Although the cefoxitin disk test is generally recognized as reliable for MRSA detection, a recent study has shown that cefoxitin may not be a good surrogate for MRSP detection by disk diffusion. 47 In the absence of an internationally recognized cefoxitin breakpoint clearly differentiating mecA-positive from mecA-negative isolates of S. pseudintermedius, we recommend that laboratories use oxacillin disk or MIC tests for detection of meticillin resistance in this and other staphylococcal species, other than S. aureus.…”
Section: Detection Of Meticillin Resistance In Staphylococcimentioning
confidence: 99%
“…As in S. aureus, methicillin resistance in SIG species is conferred by alternative penicillin binding proteins (PBPs) through the acquisition of the mecA gene, which encodes PBP2a (10). Unlike in S. aureus and the coagulase-negative staphylococci, cefoxitin has proven to be a poor surrogate indicator of methicillin resistance in SIG isolates; compared to the presence of mecA as determined by PCR, the use of cefoxitin as a surrogate indicator of methicillin resistance resulted in both major and very major errors (5). Rather, oxacillin is the appropriate surrogate for methicillin resistance in SIG isolates (Fig.…”
mentioning
confidence: 99%
“…It is recognized that this testing can be problematic for some clinical laboratories, since automated identification and susceptibility systems (such as the BD Phoenix and bioMérieux Vitek 2 systems) may not routinely report an oxacillin MIC result (5) and since some clinical laboratories do not use oxacillin for antimicrobial susceptibility testing. For this reason, immunochromatographic testing for the presence of PBP2a has been studied in SIG isolates and was shown to have 100% sensitivity and 100% specificity for the detection of methicillin resistance in a comparison with mecA PCR (10), particularly when induced PBP2a testing with cefoxitin was used (5). Isolates of the SIG can also grow on chromogenic media for the detection of methicillin-resistant S. aureus (MRSA), such as Spectra MRSA agar (Remel Microbiology Products, Lenexa, KS).…”
mentioning
confidence: 99%
See 1 more Smart Citation